Effectiveness of problem-solving therapy for depression and dysfunctional attitudes in patients after coronary artery bypass graft surgery: a randomized clinical trial - Hajitabar Firouzjaei, Nima; Masjedi Arani, Abbas; Yeke Yazdandoost, Rokhsare; Khanjani, Sajjad; Karimi, Reza; Soltani, Esmail (Researcher Bulletin of Medical Sciences, 2022)
Objective: In patients with coronary artery bypass depression is common and a major cause of mortality after graft surgery. The purpose of this study was to determine the effectiveness of problem solving therapy (PST) in patients with coronary artery bypass by assessing changes in depression and dysfunctional attitudes after graft surgery. Material and Methods: This randomized controlled trial conducted in Tehran Shahid Modarres Hospital in autumn 2018. Intervention group received PST individually in six sessions of one-hour per week and control group only received education of usual care program for two sessions. At the end of the intervention course and Follow up, both groups were tested simultaneously using the Research tools and the data were analyzed by repeated measures analysis of variance using SPSS-18 software. Results: Patients receiving PST intervention showed significant improvement based BDI (P=0.018) and DSA-26 (P= 0.009). Also, compared with Usual Care, BDI remission of rates were superior in the PST group (P= 0.001) and larger decrease on the dysfunctional attitudes in the DAS-26 at two follow up times (P= 0.001). Conclusions: These results shows that PST will be effective in reducing depression and dysfunctional attitudes in among patients with Coronary Artery Bypass Graft surgery. Then PST is an effective intervention that can improve problem-solving abilities and mental health-related in CABG surgery patients